A Syntactic Analysis Of Simple Sentence Of Various Type Used In Unexpected Journey Of The Hobbit Movie Script - Sakinatunisa, Devy Nur, Dra. Malikatul Laila, M. Hum, Dra. Siti Zuhriah Ariatmi, M.Hum (2015)
This research is aimed in identifying the types of simple sentence and describing the process of transformation used in simple sentence of types by Diane D. Bornstein in Unexpected Journey of The Hobbit movie script. The research conducted by the writer is descriptive qualitative research. The data of this research are chosen from movie script, while the data source is taken from Unexpected Journey of The Hobbit movie script. The method used by the writer in collecting data is documentation with step: reading, selecting and collecting, identifying, classifying, and coding the data. In analyzing the data, the writer is identifying types of simple sentence and describing the process of transformation of simple sentence used in Unexpected Journey of The Hobbit movie script. The result of the study shows that types of simple sentence in Unexpected Journey of The Hobbit movie script are positive emphatic sentence, negative sentence, interrogative sentence, and imperative sentence. Positive emphatic sentence consist of LV,Vi, and Vt. The study shows transformation process of simple sentence of various types.